Optimization of Scada Systems in a Remote Area by Using DTM6000 and Trunking Tier Three ( Case study in Papua) - Dhian Krisna Wahyudi, Marsul Siregar (International Journal of Advanced Science and Technology, 2020)
The objective of this paper is to provide the optimization design and installation ofSCADA (Supervisory Control And Data Acquisition) in a remote area especially for theelectric power systems in a remote area. In this paper, we proposed the optimizationdesign concept that focused on the usage method for checking and determine the locationwhere damage occurs, and so by implementing this system, it can minimize the cost forthe operation. The hardware and software installation of SCADA with the DTM6000,equipped with GPS features from Hytera Communications, Co., Ltd is proposed. TheSCADA DTM6000 equipment is operated with a Tier three (3) Radio Trunking System,where it enables the development and addition of more SCADA equipment in the future.By these Scada systems, all data can be monitored through the Control Center using NMS(Network Management System) and DWS (Dispatch work Station) software. The SCADAsystem with Radio Frequency is very useful in remote areas where telecommunicationsnetwork infrastructure is inadequate because it can cover a wide coverage area (i.e, up to21 km) with Radio Trunking Base station, This paper proposed and explain theoptimization of the technical design and the installation as well as the simulation of theapplication of the proposed system in a remote area